Nurturing Grit among Medical Students - Mirza, Tayyeba Iftikhar (Pak J Med Sci, 2021)
OBJECTIVE: To identify the learning strategies used by the medical students with high Grit for design and implementation of a three months course, to assist the medical students having low Grit. METHODS: A mixed-method study with explanatory sequential design was followed by an intervention to improve Grit amongst first year students at Foundation University Medical College from March to August 2019. Non-probability convenience sampling was used in the Phase-I. In Phase-II, through purposive sampling, students with high score on GRIT were interviewed. The interview questions were validated and piloted for clarity. All interviews were recorded, transcribed verbatim, and thematic analysis was done. The themes generated were used to design an intervention, which was implemented as a part of the curriculum for less Gritty students to see whether it can enhance Grit in them. RESULTS: A total of 133 students participated out of which, 23(17%) had a high, whereas 10(7.5%) had a low level of Grit. Five themes generated from the transcripts, namely Planning, Metacognitive skills, Mastery learning, Cognitive strategies, and Self-regulation, that led the development of an intervention abbreviated as “RESET-P- GOALS”. A Wilcoxon signed-rank test showed that the intervention did elicit a statistically significant change in the Grit score in students having low Grit (Z = -2.8, p= 0.005). CONCLUSION: Good planning, Mastery learning and self-regulation are the reasons for success of Gritty students. The learning strategies with the name “RESET-P- GOALS” are effective in enhancing Grit in students with less score on Grit.